The Effect of Promotion, Work Experience, and Motivation on Employee Performance at the Regional Revenue Agency, Kolaka Regency, Southeast Sulawesi Province - Sumiati Nurpi; Rina; Andi Hendra Syam (Fakultas Ekonomi & Bisnis Universitas Muslim Indonesia, 2023)
The purpose of this study was to analyze the effect of promotion, work experience, and motivation on employee performance at the Kolaka Regency Regional Revenue Agency, Southeast Sulawesi, and became the object of this study. The research method uses a descriptive quantitative design and SPSS 22 multiple regression analysis. The population and research sample include all 58 employees, who were collected ex post facto. The results of the study show that all research variables, namely promotion, work experience, and motivation, have a positive and significant effect on the performance of employees of the Kolaka Regency Regional Revenue Agency, Southeast Sulawesi.